Scholars and the Sea: A Historiography of the Indian Ocean - Prange, Sebastian R. ca. 20./21. Jh. (History compass, 2008)
This essay won the 2007 History Compass Graduate Essay Prize, World Section. This article surveys the historiography of the Indian Ocean to examine the problems and opportunities of using maritime spaces as frameworks for world history studies. It first considers the problem of demarcating maritime space according to different material and mental definitions. Its second part assesses different periodizations that reflect the main themes of scholarly engagement with the Indian Ocean. The final section looks at the emerging field of network studies as a new approach to the study of interconnections across the Indian Ocean world.